К биографии Ю. Г. Оксмана (По материалам Центрального государственного исторического архива Санкт-Петербурга) [Iulian Oksman’s Life Story: In Light of Some Archival Findings] - Marina Salman (Slavica Revalensia)
This article aims at describing, in detail, the life story of Iulian Oksman, the renowned expert of Russian 19th-century literature, from his birth in 1895 to his student years in Germany (1912—1913) and St. Petersburg University (1913—1917). The study is largely based on findings from the Central State Historical Archive in St. Petersburg. The documents introduced in the article verify Oksman’s exact birthdate (January 5th, 1895, O. S.), and specify some details of his university studies. They also establish as April 29th, 1916 (O. S.), the previously unspecified date in the biography of Oksman’s fellow student, Osip Mandel’shtam: on that day, Oksman passed, and Mandel’shtam failed, the exam in professor Grigory Tsereteli’s course on Ancient Greek Literature.